Efektivitas Kinerja Aparatur Sipil Negara (Asn) Bagian Tata Usaha Dalam Pengelolaan Administrasi Kepegawaian Di Dinas Ketenagakerjaan Kota Medan - Lora Marsa Hutahaean; Beby Masitho Batubara; Nina Angelia (Strukturasi: Jurnal Ilmiah Magister Administrasi Publik, 2023)
This study aims to determine the effectiveness of the performance of the State Civil Apparatus and the obstacles to the performance of the State Civil Apparatus in Administration in the Management of Personnel Administration at the Manpower Office of Medan City. This research uses qualitative research. Data were collected based on data collection techniques, namely observation, interviews and documentation. The results showed that the performance of the State Civil Apparatus (ASN) in the Administrative Section in Personnel Administration at the Manpower Service of Medan City had achieved achievements, the State Civil Apparatus was very disciplined in working on and completing personnel administration tasks in an orderly and timely manner, but did not have enough creativity because they still lacked creativity. In the absence of human resource development, the State Civil Apparatus has been able to work well together in completing any given work, very responsible for their respective duties and functions. Barriers to the Effectiveness of the Performance of the State Civil Apparatus (ASN) in the Administrative Section in the Management of Personnel Administration at the City Manpower Service are the lack of facilities, unstable internet network and applications that are not yet available for administration.